Influencia de las nuevas tecnologías en la negociación de empresas del sector logístico en la Provincia Constitucional Del Callao, Perú - Diaz Iparraguirre, Daniel Eduardo (2022)
Technological evolution has currently been shown as the paths of development and global sustainability, assuming a great influence in all economic sectors, including the logistics sector and its negotiation process, the digitization of information has become an icon of comfort. and speed to establish commercial relationships, even adding value in the selection and in the entire customer service value chain, an effect that is progressively noticeable in all production and service sectors. The document analyzes the influence of new technologies in the negotiation process and methodologically, it is a quantitative, non-experimental, applied and descriptive correlational research; using a survey conducted with officials from 34 companies that are part of the logistics sector, in the Constitutional Province of Callao, Peru. Among the hypothetical results, the correlation obtained for hypothesis 1 was 0.013, which is a significant result; Likewise, for hypothesis 2 a significant correlation of 0.01 is observed, determining whether there is an impact on the performance of the different logistics areas of the surveyed companies. On the other hand, hypothesis 4 shows a negative correlation of -0.217, that is, it has an inverse relationship. In general, the bivariate correlation was significant with a correlation coefficient of 0.01; Therefore, the general hypothesis raised is verified, since there is a high influence of technologies in the logistics negotiation processes, specifically in the preparation and closing phases. It was found that cost reduction, customer satisfaction, increased productivity and the generation of greater competitiveness of companies, due to internationalization, are the main consequences of the application of new information technologies.